Handbook of compliant mechanisms - Howell, Larry L.; Magleby, Spencer P.; Olsen, Brian M. (Brian Mark), 1983- (Chichester, West Sussex, United Kingdom ; Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
A fully illustrated reference book giving an easy-to-understand introduction to compliant mechanisms A broad compilation of compliant mechanisms to give inspiration and guidance to those interested in using compliant mechanisms in their designs, the Handbook of Compliant Mechanisms includes graphics and descriptions of many compliant mechanisms. It comprises an extensive categorization of devices that can be used to help readers identify compliant mechanisms related to their application. It also provides chapters on the basic background in compliant mechanisms, the categories o.
pt. 1. Introduction to compliant mechanisms -- pt. 2. Modeling of compliant mechanisms -- pt. 3. Synthesis of compliant mechanisms -- pt. 4. Library of compliant mechanisms.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Mechanical movements; Machinery, Kinematics of; Engineering design; Engineering design; Machinery, Kinematics of; Mechanical movements; TECHNOLOGY & ENGINEERING -- Machinery; Engineering design; Machinery, Kinematics of; Mechanical movements; Electronic books; Electronic books